Smoking habits and risk of fatal stroke: 18 years follow up of the Oslo Study. Issue 6 (December 1996) - Håheim, L L; Holme, I; Hjermann, I; Leren, P
Abstract : STUDY OBJECTIVE: To examine the risk of fatal stroke in relation to smoking habits in men screened for the Oslo study. DESIGN: The Oslo study is a prospective, cohort study of the epidemiology and preventive aspects of cardiovascular diseases in middle aged men. Screening started in May 1972 and results after 18 years of follow up are reported. PARTICIPANTS: There were 16209 men aged 40-49 years, of whom 16173 had no stroke history. Eighty five men died from stroke, of whom 48 were daily cigarettes smokers, 7 were pipe and cigar smokers, 15 smoked cigarettes and pipe or cigars daily, 11 were previous cigarette smokers, and 4 had never smoked cigarettes. MAIN RESULTS: Results of proportional hazards regression analysis adjusted for age, diastolic blood pressure, and glucose concentration showed the following rate ratios (RR) (95% confidence interval) of smoking groups compared with those who had never smoked or had previously smoked: combined cigarette and cigar or pipe smokers, RR = 6.1 (3.0, 12.5); cigarettes only, RR = 4.1 (2.3, 7.4); and pipe and/or cigars only RR = 2.2 (0.9, 5.5). The overall, age adjusted risk of smoking cigarettes daily was 3.5 and was found to increase with increasing cigarette consumption. Regardless of their smoking group, stroke cases had increased diastolic (DBP) and systolic blood pressure (SBP) when compared with men who had not had a stroke. The absolute differences in DBP and SBP between stroke cases and others for never and previous cigarette smokers versus daily smokers were twice as large: DBP, 12.1 mmHg versus 6.5 mmHg respectively and SBP, 16.0 mmHg versus 7.1 mmHg respectively. A high BMI increased the risk of fatal stroke of never and previous cigarette smokers. Men being treated for hypertension at the time of screening had three times the crude risk of fatal stroke of men who were not taking hypertensive treatment. CONCLUSIONS: Daily cigarette smoking increased the risk of fatal stroke three and a half times. Combined cigarette and pipe or cigar smoking had a higher risk than smoking cigarettes only. An increased risk was found in relation to increased daily cigarette consumption.